Public policy of sport in the municipality of Campos dos Goytacazes: "Viva o esporte" - Mecenas Pagani, Mario; Gonçalves da Matta, Ludmila; Costa Conserva, Nicaulis (Seven Editora, 2023)
The CIPP model, is a system where the evaluation has as main focus the improvement of a project or program. The aim of this study was to evaluate the sports policy "Viva o Esporte" of the municipality of Campos dos Goytacazes between 2017 and 2020. Based on the CIPP model. The methodology of bibliographic and documentary research was used, with an exploratory, descriptive and qualitative approach. From the analysis of the results it was possible to identify that the program reduced the budget in relation to the previous management, expanded the offer of sports activities, and the number of places for the practices. The number of beneficiaries increased by 19%, mainly serving people aged 6 to 17 years (68.9%). Although there was an increase in the number of activities, the modalities of athletics, badminton, beach tennis, frescoball and tennis were not offered, all of which are practiced in the municipality. The program enabled sports practice for people with disabilities, 1,009 people benefited. It is extremely necessary that the number of beneficiaries is increased. For this, it is important to offer more sports and activities to attract more participants to the program. DOI: https://doi.org/10.56238/tfisdwv1-151